Rumah Adat Batak Sebagai Simbol Identitas dan Warisan Budaya dalam Kehidupan Sehari-Hari: Melalui Kajian Strukturalisme, Antropologi Budaya, Identitas, dan Pendekatan Historis - Rosmawaty Harahap; Heri Sinta Pakpahan; Fitri Elisabetbeth Banjarnahor; Widia Tarigan; Dermina Panggabean; Nadia Ayu Syifa (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The traditional Batak house, known as Rumah Bolon, functions not only as a dwelling, but also as a symbol of identity and cultural heritage for the Batak people. This study aims to analyze the traditional Batak house using structuralist, cultural anthropological and identity theory approaches, taking into account historical and descriptive aspects. Through this study, it is hoped to discover how the traditional Batak house functions in the daily life of the Batak people, reflects cultural values and plays a role in the formation of social identity. The methods used are a literature review and structural analysis of the architectural and functional elements of the traditional Batak house, as well as descriptive historical and cultural studies. The research results show that the traditional Batak house has a deep meaning in the social, cultural and spiritual contexts of the Batak community, as well as the importance of preserving the traditional house as a cultural symbol that still stands today.